TEACHING IDIOMS WITH PROPER NAMES TO ESL STUDENTS - Koyshekenova, T. (SCIENCE and SOCIETY, 2025)
This article deals with the problems of teaching idioms which contain proper names aims and focuses on explaining their meanings, origin and examples to ESL students. Proper name idioms present troublesome expressions that cannot be translated word by word, that’s why they must be given in a special dictionary as ready-made expressions with their meanings, origins, or translations.